Different antigenicities of the N‐terminal region of cellular and scrapie prion proteins. (November 2013) - Ushiki‐Kaku, Yuko; Iwamaru, Yoshifumi; Masujin, Kentaro; Imamura, Morikazu; Itohara, Shigeyoshi; Ogawa‐Goto, Kiyoko; Hattori, Shunji; Yokoyama, Takashi
ABSTRACT Limited information is available about conformational differences between the abnormal isoform of prion protein (PrPSc) and cellular prion protein (PrPC) under native conditions. To clarify conformational differences between these two isoforms, PrP‐deficient mice were immunized with brain homogenates of normal and scrapie‐infected animals. All mice generated anti‐PrP antibodies. Peptide array analysis of these serum samples revealed a distinctive epitope of PrPSc consisting of QGSPGGN (PrP41–47) at the N‐terminus. This study demonstrated a conformational dissimilarity at the N‐terminus between PrPSc and PrPC, a finding that may provide novel information about conformational features of PrPSc.